Anchoring Sub‐Nanometer Pt Clusters on Crumpled Paper‐Like MXene Enables High Hydrogen Evolution Mass Activity. (13th January 2022) - Wu, Yucai; Wei, Wei; Yu, Ruohan; Xia, Lixue; Hong, Xufeng; Zhu, Jiexin; Li, Jiantao; Lv, Lei; Chen, Wei; Zhao, Yan; Zhou, Liang; Mai, Liqiang
Abstract: Platinum (Pt)‐based electrocatalysts are the benchmark catalysts for hydrogen evolution reaction (HER); however, they are limited by the scarcity and high price. Introducing an adequate substrate to disperse and anchor Pt‐based species is a feasible pathway to improve the utilization efficiency. Herein, a quick and continuous spray drying route is proposed to fabricate 3D crumpled Ti3 C2 T x MXene loaded with sub‐nanometer platinum clusters (Pt/MXene). The 3D crumpled structure inhibits the restacking of layered MXene nanosheets and guarantees the fully exposure of Pt clusters. The as‐prepared catalyst exhibits excellent HER performances comparable to commercial Pt/C, including a low overpotential of 34 mV to reach a current density of 10 mA cm −2, a superior mass activity (1847 mA mgPt −1 ), a small Tafel slope (29.7 mV dec −1 ), and a high turnover frequency (10.66 H2 s −1 ). The improved activity of Pt/MXene can be attributed to the charge transfer from Pt clusters to MXene, which weakens the hydrogen adsorption, as evidenced by the density functional theory calculations. The present contribution proposes a novel strategy to anchor low‐mass‐loading sub‐nanometer precious metal clusters on crumpled MXene with fully exposed active sites for catalysis. Abstract : A crumpled MXene‐supported platinum (Pt) cluster catalyst is rationally designed. The anchoring of Pt clusters on crumpled MXene weakens the hydrogen adsorption and endows the catalyst an optimized electronic state. The obtained Pt/MXene demonstrates a superior hydrogen evolution reaction mass activity seven times to that of commercial Pt/C.